ANALYSIS OF ENGLISH LEARNING DIFFICULTIES IN THE VOCABULARY ASPECTS OF GRADE 3 STUDENTS OF UPT SD NEGERI 060866 - Eva Betty Simanjuntak; Dea Yuanita Nasution; Erni Telaumbanua; Asih Asari Tanjung; Donprico Purba; Natania Gabriella Nainggolan (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to see and understand the difficulties experienced by grade 3 students in learning English at UPT SD Negeri 060866. In the learning process, there are still many students who do not understand basic vocabulary, are confused about pronouncing words, and have difficulty following simple instructions in English. In addition, several factors such as lack of practice, shyness to speak, and lack of confidence are also major causes. This study uses a descriptive approach by observing learning activities in the classroom and conducting simple interviews with teachers. As a result, it was found that students need more interactive learning methods, the use of visual media, and repetitive exercises to make the material easier to understand. By understanding these difficulties, teachers can adjust learning strategies to better suit the needs of grade 3 students